Constructivist instruction : success or failure? - Tobias, Sigmund; Duffy, Thomas M. (Routledge, 2009)
Constructivist Instruction: Success or Failure? brings together leading thinkers from both sides of the hotly debated controversy about constructivist approaches to instruction. Although constructivist theories and practice now dominate the fields of the learning sciences, instructional technology, curriculum and teaching, and educational psychology, they have also been the subject of sharp criticism regarding sparse research support and adverse research findings. This volume presents:the evidence for and against constructivism;the challenges from.